2001
DOI: 10.1046/j.1440-0952.2001.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Gem‐bearing basaltic volcanism, Barrington, New South Wales: Cenozoic evolution, based on basalt K–Ar ages and zircon fission track and U–Pb isotope dating

Abstract: Barrington shield volcano was active for 55 million years, based on basalt K-Ar and zircon fission track dating. Activity in the northeast, at 59 Ma, preceded more substantial activity between 55 and 51 Ma and more limited activity on western and southern flanks after 45 Ma. Eruptions brought up megacrystic gemstones (ruby, sapphire and zircon) throughout the volcanism, particularly during quieter eruptive periods. Zircon fission track dating (thermal reset ages) indicates gem-bearing eruptions at 57, 43, 38, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…The mantle lithosphere below Barrington, however, clearly contains amphibole-bearing lithologies that can potentially produce corundum-normative felsic melts (Sutherland et al, 1998b). Zircon megacrysts at Barrington show magmatic growth features and although their fission track ages are reset by basalt transport events, their U-Pb formation ages cluster at 50À60 Ma and 45À46 Ma (Sutherland and Fanning, 2001). Thus, magmatic sapphire and zircon formation below the Barrington field was closely related to the Palaeogene basaltic magmatism.…”
Section: Barrington Sapphire Sourcesmentioning
confidence: 97%
See 1 more Smart Citation
“…The mantle lithosphere below Barrington, however, clearly contains amphibole-bearing lithologies that can potentially produce corundum-normative felsic melts (Sutherland et al, 1998b). Zircon megacrysts at Barrington show magmatic growth features and although their fission track ages are reset by basalt transport events, their U-Pb formation ages cluster at 50À60 Ma and 45À46 Ma (Sutherland and Fanning, 2001). Thus, magmatic sapphire and zircon formation below the Barrington field was closely related to the Palaeogene basaltic magmatism.…”
Section: Barrington Sapphire Sourcesmentioning
confidence: 97%
“…The analyses used similar methods and statistical treatments to those reported for zircon megacrysts from the Barrington basaltic gemfields (see Sutherland and Fanning, 2001;Roberts et al, 2004).…”
Section: Zircon Geochronologymentioning
confidence: 99%
“…Source signatures differ across the East Australian Plume System zone, with phlogopite-enriched sources for western leucitites, OIB-like plume components for the central volcanoes and an EMI plume and 'long term depleted' upper mantle interaction for eastern basaltic seamounts. Some basalts indicate interaction of OIB-like melts with metasomatised amphibole (+apatite)-enriched mantle lithosphere (O'Reilly & Zhang 1995;Sutherland et al 1996Sutherland et al , 2002Sutherland & Fanning 2001;Zhang et al 2001). They were called HIMU-like in their trace-element patterns, but lacked the high radiogenic Pb of true HIMU (Zhang et al 2001).…”
mentioning
confidence: 99%
“…Some basalts include amphibole geochemical imprints and HIMU isotopic features but not Tasman HIMU trace-element ratios (Sutherland et al 1996). Others show Tasman HIMU-like trace-element ratios but lack amphibole (+apatite) geochemical imprints, while coexisting basalts show amphibole geochemical imprints but lack Tasman HIMU-like trace-element ratios (Sutherland & Fanning 2001;Sutherland et al 2001). The amphibole imprints largely occur outside the East Australian Plume System migratory fields, but minor diluted contributions are found within East Australian Plume System basalts (Sivell & Ashley 2000).…”
mentioning
confidence: 99%
“…Yui et al, 2003) and gem-bearing basaltic volcanism has already been suggested to derive from a mantle plume activity (Sutherland and Fanning, 2001). …”
Section: Accepted M Manuscriptmentioning
confidence: 99%